Doktryna rasowa Niezależnego Państwa Chorwackiego 1941–1945 - Cesarz, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The Independent State of Croatia Nezavisna Država Hrvatska, established in 1941 after Adolph Hitler’s conquest of Yugoslavia, soon became unstable and hard-pressed to control its territory. Remaining under formal authority of the Axis, in fact NDH pursued its own policy towards ethnic and national minorities. Although strongly influenced by German Nazi regulations and racial ideas, the Ustascha regime introduced original official race doctrine, reflecting complex ethnic structure of the new satellite of the Axis, which included even more oppressive than originally German laws concerning Jews and Gypsies and used the concept of Croatian-Arian descent. The article highlights the concept of Dynaric-Nordic origin of Croats as developed by ideologues of the Ustascha regime which was accepted in general by the Nazis. The vision of Asiatic, Gypsy-Jewish Serbs created for the propaganda purposes is also examined. Portrayed as second-rate citizens, naturally susceptible to bolshevism, Serbian minority was identified as a main national enemy in historical and racial terms. The racial decrees of Ante Pavelic’ government are also covered and short analysis of how the official state doctrine influenced practical undertakings of the Ustascha is provided.
Keywords: Niepodległe Państwo Chorwacji; rasizm; reżim Ustascha; nazism